Dom Casmurro:a encenação de um julgamento : na adaptação cinematográfica de Moacyr Góes e de Paulo César Saraceni - Silva, Almir Guilhermino da (2007)
The thesis Dom Casmurro: the staging of a trial results from a research on the adaptation of the novel Dom Casmurro, by Machado de Assis, in the Paulo César s Capitu and Moacyr Góes Dom movies. Charles Sanders Peirce s semiotic theory, mainly on the view of Lúcia Santaella, grounded the critical analysis. The study assumes the idea that behind Dom Casmurro-memories, underlies a Dom Casmurro-acting. Helen Caldwell points out a Shakespeare-follower Machado de Assis. Furthermore, critics like Barreto Filho, Magalhães Jr., Raimundo Faoro and Massaud Moisés show the route of the Machadian writing. The novelist had also been a drama and literary critic, an essayist, a poet, and author of comedies, the reason why his narrative sign has been influenced by the dramatic one. In each chapter, a possible scene; sentences as rubrics, causing the text to be a whole index. A more attentive reader will feel like watching while reading a novel turning into a performance. From the view of Luiz Fernando Ramos, on the didaskalias, and the floating spaces, by Fiona Hugues, the Machadian rubrics have been studied as an articulated system in three semantic cores: the rebuilt house, as a setting; the visual poetical plan, as the perspective of the narrative; and the metalanguage, revealing both the book as a parody of Otelo and the narrator s intent to turn it into an spectacle. Having such cores as referentials, the adaptations for movies have been taken as the dynamic interpretant of the novel, that is, as effectively generated effects. According to Thäís Diniz, the analysis characterizes the movies as transcreations. The adaptations are not mimetic as a whole due to the cultural context which constitutes the reception process of the work.